Novel treatment options for coagulant and potable sludge - Murray, C. A. (Cranfield University, 2005)
increases in coagulant required to remove sufficient quantities of natural organic matter (NOM) to ensure compliance with trihalomethane (THM) regulations lead to an increase in the volume of potable sludge generated. Here options to treat the sludge or reduce the amount of sludge produced are assessed. The results from assessing advanced oxidation processes for the treatment of potable sludge showed that although feasible it would be more advantageous to remove the NOM from the water via a process that generates less sludge. For the removal of NOM the main focus was on the adsorption of NOM onto TiO2 powder and this was optimised in terms of the removal of bulk water parameters, namely dissolved organic carbon (DOC) and ultraviolet (UV) absorbance at 254 m (UV254). The results showed that both the DOC and UV254 absorbance could be reduced by over 90%. Secondly the immobilisation of TiO2 as a thin lm coated on a supporting substrate was evaluated. To obtain a uniform coating was complex and the NOM removal was much poorer than that achieved using the TiO2 powder due to the reduced surface area. To overcome the complex issue of separating the TiO2 powder from the treated water larger pellets sized TiO2 particles were used as a adsorbent coupled with side-stream UV regeneration. Results from both bench and pilot scales showed that the DOC concentration could be reduced by 86% and the UV254 absorbance by 75%. In addition low M compounds which are untouched by conventional coagulation were removed. Combining NOM adsorption onto TiO2 pellets with ferric coagulation increased the reduction in UV254 absorbance to 94% at a reduced coagulant dose. This reduction in coagulant dose of over 80% will have a major impact on the volume of potable sludge generated.